The relationship between stressful events, emotion dysregulation, and anxiety symptoms among youth: longitudinal support for stress causation but not stress generation. Issue 2 (4th March 2021) - Schneider, Rebecca L.; Long, Erin E.; Arch, Joanna J.; Hankin, Benjamin L.
ABSTRACT: Introduction: There is a clear bi-directional link between stressful events and depressive symptoms in adolescence, but the directionality of this link for anxiety symptoms remains underexamined. We critically evaluate the longitudinal relationship between stressors and anxiety among youth. Specifically, we examine whether stressors predict anxiety symptoms over a 1.5-year period (stress causation), and whether anxiety symptoms predict stressors over this period (stress generation). We examine potential influencing factors, including stressor type (independent vs. dependent) and emotion dysregulation (nonacceptance; goal-directed difficulty). Methods: Social, separation, and physical anxiety symptoms, and frequency and stressor type, were assessed every 3 months for 1.5 years among community youth ( n = 528, ages 8–17). Baseline emotion dysregulation was assessed. Time-lagged analyses evaluated the bi-directional relationship of stress and anxiety over time, controlling for previous anxiety and depression. Results: Interpersonal stressors predicted subsequent physical and social anxiety symptoms, but anxiety did not predict subsequent stressors. Both nonacceptance and goal-directed difficulties predicted subsequent anxiety symptoms and stressors, but did not moderate the relationship. Conclusion: The findings supported the stress causation model for youth anxiety, but not the stress generation model. Nonacceptance and goal-directed difficulty predicted greater subsequent anxiety symptoms and stressors. We discuss implications for prevention and intervention.